An Imagery Analysis of the Short Film Black Mamba in the SM Culture Universe: An Aesthetic Feature of Films - Aliyah, Nur Himmatul; Warno Edi; Cubarsi, Hagehowa (Journal of Language and Literature Studies, 2025)
This study examines the use of imagery in the short film Aespa Ep.01: Black Mamba within the SM Culture Universe, employing a qualitative descriptive method and a case study approach. Grounded in literary theory, the research conceptualizes imagery—visual, auditory, kinesthetic, organic, olfactory, gustatory, and tactile—as essential in constructing sensory and emotional meaning within a narrative. Drawing on the frameworks of Perrine, Klarer, and Abrams, the study treats film as a literary text capable of conveying complex messages through symbolic and sensory elements. Data were collected through repeated observation of the short film and analyzed by categorizing and interpreting the types of imagery. A total of 110 instances of imagery were identified. The findings reveal that visual imagery is the most dominant, contributing to the film’s futuristic and digital atmosphere. Kinesthetic and organic imagery enhance the narrative by illustrating physical action and internal emotion, while auditory imagery supports both the storyline and philosophical themes. Olfactory, gustatory, and tactile imagery were found to be minimal or absent. The study concludes that imagery in the film serves not only as an aesthetic feature but also as a medium for expressing deeper meanings related to digital identity, emotional experience, and the convergence of virtual and real worlds. These findings underscore the potential of visual storytelling as a literary tool in contemporary media. Future research is encouraged to explore visual semiotics, spatial symbolism, and comparative media analysis to further illuminate the dynamics of digital narratives.